2009
DOI: 10.1590/s1516-31802009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure therapy (vacuum) for wound bed preparation among diabetic patients: case series

Abstract: CONTEXT: Complications from diabetes mellitus affecting the lower limbs occur in 40 to 70% of such patients. Neuropathy is the main cause of ulceration and may be associated with vascular impairment. The wound evolves with necrosis and infection, and if not properly treated, amputation may be the end result. Surgical treatment is preferred in complex wounds without spontaneous healing. After debridement of the necrotic tissue, the wound bed needs to be prepared to receive a transplant of either a graft or a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
(42 reference statements)
0
10
0
6
Order By: Relevance
“…Other causes of wounds reported in literature for which NPWT has been used for the integration of STSG include diabetic wounds,[13] hidradenitis cystica and amputation stump wounds,[5] wounds following excision of irradiated extremity sarcomas,[14] necrotising fasciitis and associated pubic bone osteomyelitis,[15] Fournier's gangrene,[16] chronic leg ulcers,[17] over punch grafts after excision of melanoma feet[18] and over radial forearm free flap donor sites. [19] NPWT has also been used for securing skin grafts to microvascular free flaps[20] and for the vulvovaginal reconstruction with skin grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of wounds reported in literature for which NPWT has been used for the integration of STSG include diabetic wounds,[13] hidradenitis cystica and amputation stump wounds,[5] wounds following excision of irradiated extremity sarcomas,[14] necrotising fasciitis and associated pubic bone osteomyelitis,[15] Fournier's gangrene,[16] chronic leg ulcers,[17] over punch grafts after excision of melanoma feet[18] and over radial forearm free flap donor sites. [19] NPWT has also been used for securing skin grafts to microvascular free flaps[20] and for the vulvovaginal reconstruction with skin grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest skin disorders are xerosis and pruritus 8,9) . Recent epidemiological studies have demonstrated that the prevalence of pruritus among patients who are adequately dialyzed remains high, ranging between 42 and 75% [10][11][12] . Uremic pruritus is very frustrating for patients since no effective treatment for relief of the itching has been demonstrated.…”
Section: Local Factorsmentioning
confidence: 99%
“…In clinics, the incidence rate of diabetic foot ulcer, deep burn, bedsore, severe varicosity, obliterans of lower extremities, ulcers caused by severe trauma and others, especially chronic refractory skin ulcer has increased significantly which greatly influence the patients survival rate (1). After debridement, medical dressing for periodic dressing change is a common treatment, but the effective rate is only 40–60%, and the infection rate still reaches 10–30% (2).…”
Section: Introductionmentioning
confidence: 99%